Multiplexed Phosphoproteomic Study of Brain in Patients with Alzheimer's Disease and Age-Matched Cognitively Healthy Controls - Sathe, Gajanan (OMICS, 2020)
Alzheimer's disease (AD) is the most common neurodegenerative disorder caused by neuronal loss that results in cognitive and functional impairment. Formation of neurofibrillary tangles composed of abnormal hyperphosphorylation of tau protein is one of the major pathological hallmarks of AD. Importantly, several neurodegenerative disorders, including AD, are associated with abnormal protein phosphorylation events. However, little is known thus far on global protein phosphorylation changes in AD. We report a phosphoproteomics study examining the frontal gyrus of people with AD and age-matched cognitively normal subjects, using tandem mass tag (TMT) multiplexing technology along with immobilized metal affinity chromatography to enrich phosphopeptides. We identified 4631 phosphopeptides corresponding to 1821 proteins with liquid chromatography-mass spectrometry (MS)/MS analysis on an Orbitrap Fusion Lumos Tribrid mass spectrometer. Of these, 504 phosphopeptides corresponding to 350 proteins were significantly altered in the AD brain: 389 phosphopeptides increased whereas 115 phosphopeptides decreased phosphorylation. We observed significant changes in phosphorylation of known as well as novel molecules. Using targeted parallel reaction monitoring experiments, we validated the phosphorylation of microtubule-associated protein tau and myristoylated alanine-rich protein kinase C substrate (MARCKS) in control and AD (Control = 6, AD = 11) brain samples. In conclusion, our study provides new evidence on alteration of RNA processing and splicing, neurogenesis and neuronal development, and metabotropic glutamate receptor 5 (GRM5) calcium signaling pathways in the AD brain, and it thus offers new insights to accelerate diagnostics and therapeutics innovation in AD.